Preliminary Investigation of Microplastics in Sediments from Industrial Manufacturing Waste Sources - Oanh, Doan Thi; Thuy, Duong Thi; Huong, Nguyen Thi Nhu; Quynh, Hoang Thi; Hieu, Phung Duc; Vu, Dang Minh; Nguyet, Vu Thi; Quynh, Le Thi Phuong; Cuong, Bui Van; Thuong, Bui Huyen (VNU Journal of Science: Natural Sciences and Technology, 2022)
Microplastics (particles with a size of less than 5 mm) are a rising environmental problem. Microplastics can disseminate in the air and accumulate in sediments as well as in microorganisms and humans, due to their small size. Sediment is considered to be the major repository of microplastics, particularly those of the PE type. Microplastics in massive amounts accumulated in sediments, perhaps as a result of point sources or diffuse contamination. Microplastic contamination can spread from industrial production facilities, urban areas, agricultural areas, or the air. The current study was carried out to explore the occurrence of MPs in sediments at discharge sources by evaluating 27 sediment samples taken from 9 distinct waste sources from industrial activity locations to determine the amount of microplastic contamination in sediments at discharge sources. Microplastics with relatively high density were found in all sediment samples in this research, ranging from 2,900 to 238,200 particles/kg dw. The most prevalent microplastics detected in sediment samples at these sites were fibers and fragments, accounting for 59-94% and 6-41%, respectively. Fiber microplastics ranged in size from 1000 to 9,000 µm, whereas fragment microplastics ranged from 200,000 to 2,100,000 µm 2 . Microplastics with < 1000 µm and 1000-2000 µm sizes accounted for a significant portion of the total, reaching 21.05-37.84% and 39.74-61.17%, respectively. The hue of microplastic particles in sediment samples obtained was highly varied.